Analisis Kepuasan Pengguna Terhadap Layanan Arsip di Sekolah Vokasi Institut Pertanian Bogor - Marjono, Marjono; Laila, Ratu Anna Nazla; Fatimah, Imas (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
Service quality is very important, because its role is related to the interests of users, both the interests of internal and external users as a whole. This research aims to determine the level of satisfaction and performance assessment of archive services. The data collection method uses a literature study model and questionnaires. Data analysis uses primary data obtained from the results of questionnaire analysis, and secondary data obtained from a literature review. Respondents in this research were education staff, lecturers and students. The level of satisfaction with the quality of archival services at the IPB College of Vocational Studies based on CSI analysis was 81.76%, indicating that in general respondents were very satisfied with the quality of archival services. The results of the suitability analysis show that the relationship between expectations and the quality of archival services shows the highest gap in indicator A3(-0.502), where respondents expect the complete availability of required records, and the lowest gap in indicator Y3 (-0.364), namely staff politeness and the information provided is clearly understood. The conformity level of 90.24% indicates that the quality of archival services is considered good and service performance is in line with expectations. IPB College of Vocational Studies must consider human resource competency and ease of access. Human resourcecompetency, ease of access, is one of the issues that needs to be paid attention to by the IPB College of Vocational Studies. One of the managerial implications is increasing capabilities in the field of archives and recommendations for a comprehensively integrated system for IPB. It is hoped that researchers and stakeholders will accept development ideas and practical contributions in the form of strategic understanding and references.